Effect of cycloheximide on development of methotrexate resistance of Chinese hamster ovary cells treated with inhibitors of DNA synthesis. - Sherwood, S W (1988)
We examined the effects of 18 h of incubation of Chinese hamster ovary (CHO K1) cells with cycloheximide, hydroxyurea, and aphidicolin. Treatment of cells with cycloheximide alone at a concentration adequate to inhibit DNA synthesis to less than 10% of control was significantly less cytotoxic and clastogenic than treatment with hydroxyurea or aphidicolin, did not induce unbalanced cellular growth, and had no effect on the frequency of resistant cells in methotrexate selections compared with control cells. When combined with hydroxyurea or aphidicolin and compared with the effects of either drug alone, cycloheximide blocked the induction of unbalanced growth during drug treatment, reduced the frequency of chromosomal aberrations in recovering cell populations, and decreased cell killing. In addition, the increased frequency of methotrexate-resistant cells observed after treatment with hydroxyurea or aphidicolin was eliminated when cycloheximide was present during drug treatment.